Analysis of Basic Dribbling Technique Skills in Football Games - Marsuna, Marsuna (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research aims to determine the analysis of basic dribbling technical abilities in the game of soccer. This research is quantitative descriptive research in observing phenomena in the field through tests and measurements. The test was carried out at SMK Negeri 5 South Konawe with the entire population of 30 people actively participating in extracurricular activities. The sampling technique uses total sampling, namely the entire population, so that in this study the sample was 30 people. The test instrument used is the dribbling test. The data analysis technique uses descriptive statistics with percentages. The results of this research are that the majority of students have sufficient dribbling abilities, with 63% of the total students analyzed falling into this category. This shows that the majority of students have sufficient basic dribbling skills to play soccer. A small portion of students (10%) are still in the poor category, while other students (7%) have achieved a high level of dribbling skills in the very good category. Thus, the distribution of dribbling abilities among students was investigated. This can be a basis for coaches and educators to design appropriate training programs, taking into account individual needs and providing appropriate support to improve dribbling skills.